2015
DOI: 10.5489/cuaj.3356
|View full text |Cite
|
Sign up to set email alerts
|

Large retroperitoneal hemangioma encompassing the renal vein

Abstract: Large retroperitoneal hemangioma encompassing the renal vein E894Cite as: Can Urol Assoc J 2015;9(11-12):E894-6. http://dx.doi.org/10.5489/cuaj.3356 Published online December 14, 2015. AbstractRetroperitoneal hemangioma (RH) is a rare and benign vascular malformation. RH may be detected incidentally or present with symptoms due to local invasion of adjacent structures. Management options include surgical resection, as well as serial observation with routine imaging. We describe a retroperitoneal hemangioma enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 15 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…On T1-weighted imaging, it usually shows low signal intensity, whereas in T2-weighted imaging, hemorrhage can be interpreted with high intensity. 5,6,14 The retroperitoneal cavernous hemangioma is very difficult to diagnose before surgery. The differential diagnosis included GIST, lymphangioma cyst, or primary retroperitoneal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On T1-weighted imaging, it usually shows low signal intensity, whereas in T2-weighted imaging, hemorrhage can be interpreted with high intensity. 5,6,14 The retroperitoneal cavernous hemangioma is very difficult to diagnose before surgery. The differential diagnosis included GIST, lymphangioma cyst, or primary retroperitoneal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…MRI (Magnetic resonance imaging) may help with the diagnosis. On T1‐weighted imaging, it usually shows low signal intensity, whereas in T2‐weighted imaging, hemorrhage can be interpreted with high intensity 5,6,14 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas on T2-weighted imaging, hemorrhage, and hyalinization of tissue can often be interpreted with high intensity within the tumor. [ 15 17 ] Although we did offer the option of a MRI examination before the operation, the patient declined and instead surgery was performed after a physical exam.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal Hemangioma is very rare tumour. There is no obvious gender predisposition for retroperitoneal hemangioma and cases have been reported in both children and adults (Mossanen et al, 2015). Hemangioma is histopathologically classied into capillary, cavernous, a r t e r i o v e n o u s a n d v e n o u s t y p e s .…”
Section: Figure 1-axial and Coronal Computed Tomography Image; Tumourmentioning
confidence: 99%
“…The tissue-specic multiplanar capability of high-resolution MRI allows better tumour localization and internal characterization, thereby serving as a road map for surgical planning (Shanbhogue et al, 2012). The few reported cases of hemangioma in whom MRI was performed revealed a low signal intensity on the T1-weighted image and high signal intensity on the T2-weighted image (Igarashi & Hanazaki, 1998) (Matsuoka et al, 2018) and have been suggested to represent the haemorrhage and hyalinization of tissue (Mossanen et al, 2015). Malignant vascular tumours such as angiosarcoma, epithelioid hemangioendothelioma, and Kaposi sarcoma resemble hemangiomas ,but these tumours often have low signal central regions on T2-weighted images or multiple lesions distinguishing typical features of hemangioma (Worawattanakul et al, 1997) (Buetow et al, 1994).The imaging ndings of most retroperitoneal soft tissue tumours are nonspecic and a denitive diagnosis most often is established only by histopathologic evaluation.…”
Section: Figure 1-axial and Coronal Computed Tomography Image; Tumourmentioning
confidence: 99%